Recent Publications (Quarterly Journal of Economics, 1937)
Recent Publications The Quarterly Journal of Economics, Volume 51, Issue 2, February 1937, Pages 388–391, https://doi.org/10.1093/qje/51.2.388 Published: 01 February 1937